If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + 3y + -4 = 0 Reorder the terms: -4 + -6x + 3y = 0 Solving -4 + -6x + 3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + -6x + 4 + 3y = 0 + 4 Reorder the terms: -4 + 4 + -6x + 3y = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -6x + 3y = 0 + 4 -6x + 3y = 0 + 4 Combine like terms: 0 + 4 = 4 -6x + 3y = 4 Add '-3y' to each side of the equation. -6x + 3y + -3y = 4 + -3y Combine like terms: 3y + -3y = 0 -6x + 0 = 4 + -3y -6x = 4 + -3y Divide each side by '-6'. x = -0.6666666667 + 0.5y Simplifying x = -0.6666666667 + 0.5y
| 4ax-2a= | | x^7=1000 | | 8y^2=x^2-x^4 | | 7(x-2)+3(x+1)-2(x-1)=3(2x-5)-2 | | 6m+3=2m+15 | | x^3+x^2+5=155 | | x^3+x^2+5=156 | | x^3+x^2+5=45 | | 3z/7-5=9 | | z/7-2=10 | | 3z/7-6=-1 | | tan(5x+0.5)=3 | | senx=015 | | 7x-2=-7 | | 64=y/4 | | 7.5x+9.6(23-x)=204 | | 50c^2-98d^2=0 | | 72x^2-17x=0 | | 50d^2-98d^2=0 | | 7.5x+9.6(23-x)=20 | | 10h-13=17 | | 4z/9-8=-7 | | 4+3x+x+6= | | 15+8=63 | | Uw+vw=0 | | 5w-6=1 | | 6m+4=24 | | x^2-11y^2=1 | | (x-6)(x-6)-(x-4)(x-9)=x | | -14+4=5(x+6)-3(3-x) | | x^2-32x+144=0 | | -3x^2+6x+6=0 |